Development of medication reminder WhatsApp Bot application to improve medication adherence in pregnant women with hypertension - Hesti Kurniasih; Septerina Purwandani Winarso; Qona Lutfi Sartika (Medisains)
Background: Pregnant women's compliance with taking medication regularly is essential and supports the success of therapy. If pregnant women do not comply with taking medication, this can hurt the development of the disease and cause unexpected complications. Non-communicable diseases cause most cases of death in pregnant women. This is the basis for researchers to create a medication reminder system.